On W2-curvature tensor of a generalized complex space forms - Bharathi, M. C. (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
In the present paper we study certain curvature conditions on W2-curvature tensor. We study W2-semisymmetric, W2-flat generalized complex space forms. Also W2 Â· S = 0 and W2 Â· R = 0 on generalized complex space forms are studied. Key words:- Generalized complex space forms, W2-semisymmetric, W2-flat. AMS Subject Classification (2010): 53C15, 53C20, 53C21, 53C25, 53D10, 53C55;